2018
DOI: 10.1016/j.stem.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Loss of H3K27me3 Imprinting in Somatic Cell Nuclear Transfer Embryos Disrupts Post-Implantation Development

Abstract: Animal cloning can be achieved through somatic cell nuclear transfer (SCNT), although the live birth rate is relatively low. Recent studies have identified H3K9me3 in donor cells and abnormal Xist activation as epigenetic barriers that impede SCNT. Here we overcome these barriers using a combination of Xist knockout donor cells and overexpression of Kdm4 to achieve more than 20% efficiency of mouse SCNT. However, post-implantation defects and abnormal placentas were still observed, indicating that additional e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
127
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(143 citation statements)
references
References 62 publications
14
127
1
1
Order By: Relevance
“…In addition to our results on the MT2A deletion allele, the importance of the LIT-induced igDMR for allelic usage is also supported by the observation of imprinted expression at Slc38a4 in embryonic and adult epiblast-derived tissues in which the igDMR, but not the intragenic H3K27me3 domain, is present ( Supplementary Fig. 10 ) 33,49 . The paradoxical critical role of two different maternal epigenetic marks laid down in two different regions of the Slc38a4 locus may be reconciled by the fact that an alternative annotated TSS of the Slc38a4 gene is located downstream of the igDMR and is embedded within the intragenic region enriched for H3K27me3 described by Inoue and colleagues 47 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition to our results on the MT2A deletion allele, the importance of the LIT-induced igDMR for allelic usage is also supported by the observation of imprinted expression at Slc38a4 in embryonic and adult epiblast-derived tissues in which the igDMR, but not the intragenic H3K27me3 domain, is present ( Supplementary Fig. 10 ) 33,49 . The paradoxical critical role of two different maternal epigenetic marks laid down in two different regions of the Slc38a4 locus may be reconciled by the fact that an alternative annotated TSS of the Slc38a4 gene is located downstream of the igDMR and is embedded within the intragenic region enriched for H3K27me3 described by Inoue and colleagues 47 .…”
Section: Discussionsupporting
confidence: 84%
“…To validate previously identified maternally methylated imprinted gDMRs (igDMRs) 2124 , we interrogated DNAme profiles from published whole genome bisulfite sequencing data from gametes, placenta and somatic tissues ( Supplementary Table 1 ) 56 . Specifically, we identified regions that are hypermethylated (> 70% DNAme) in oocytes, hypomethylated (< 30% DNAme) in sperm, retain DNAme (>25%) in the blastocyst, and show 35-65% DNAme in placenta (purified first-trimester cytotrophoblast; CT) or at least one adult somatic tissue 4,5,7,8,18,19,29,40,41,44,47,49,57–69 . We further validated and refined this list by only including gDMRs harboring either reported maternal, monoallelic or bimodal DNAme in the placenta and/or at least one somatic tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Related studies have demonstrated that the ectopic expression of Xist in SCNT derived embryos could be corrected by siRNA-Xist, leading to more than a 10-fold increase in the birth rate of male clones [3, 49, 50]. To examine whether the combination of siRNA-Xist and siRNA-6B could further improve SCNT embryonic full-term development.…”
Section: Resultsmentioning
confidence: 99%
“…Bai et al claimed that H3K27me3 removal corrected SCNT-specific aberrant XCI status in cloned embryos. This was especially of interest since it was recently reported that H3K27me3 serves as the imprinting mark of Xist, and loss of H3K27me3 induces Xist ectopic expression [47, 50]. To further determine the role of KDM6A in the XCI of SCNT, we injected KDM6A mRNA (1,000 ng/μl) into SCNT embryos, and found that the developmental efficiency of SCNT embryos was reduced, while many X-linked genes were consistently repressed.…”
Section: Discussionmentioning
confidence: 99%
“…3e). Notably, H3K27me3 was recently implicated in transcriptional silencing of genes subject to non-canonical maternal imprinting in the mouse 41,57 . These results reveal that at the 2C stage, the paternal and maternal alleles of a subset of PDA loci are distinctly marked by DNAme and H3K27me3, respectively.…”
Section: Most Pda Target Genes Are Expressed During Spermatogenesis Amentioning
confidence: 99%